In Vitro Management of Karnal Bunt of Wheat by Using Fungicides and Botanicals - Kaur, Anmolpreet; Kumar, Rajnish; Gill, Enampreet Kaur (International Journal of Economic Plants, 2025)
The study was conducted during November, 2023–April, 2024 at laboratory of Plant Pathology, PG Department of Agriculture, Khalsa College, Amritsar, Punjab, India to investigate the comparative analysis of two different methods of management of Karnal bunt i.e., through botanicals and fungicides. Efficacy of four botanicals viz., lantana (Lantana camara), eucalyptus (Eucalyptus tereticornis), datura (Datura strimonium) and neem (Azadirachta indica) was tested at three different concentrations (10, 25, 50%) against Neovossia indica the causal agent of Karnal bunt in wheat. Additionally, five fungicides namely, Tilt 25 EC, Antracol 70 WP, Score 25 EC, Nativo 75 WG and Dithane M-45 75 WP was evaluated at three different concentrations (50, 100, 150 ppm) under in vitro conditions on inhibition in mycelial growth of Neovossia indica. Results revealed that Datura showed the highest average mycelial inhibition of 55.03% followed by Neem (46.42 %) and Eucalyptus (37.63%) and Lantana was found least effective with average mycelial inhibition of 11.33%. Among the five tested fungicides, Tilt 25 EC was found to be the most effective with maximum average mycelial growth inhibition of 95.40% followed by Nativo 75 WG (87.28%), Score 25 EC (66.51%) and Dithane M-45 75 WP (62%). However, the minimum average mycelial inhibition of 47.69% was recorded in Antracol 70 WP. The study highlighted the potentiality of both botanicals and fungicides in managing Karnal bunt, with varying degrees of efficacy.